2013
DOI: 10.1111/sji.12102
|View full text |Cite
|
Sign up to set email alerts
|

PGE2 Contributes to In vitro MSC‐Mediated Inhibition of Non‐Specific and Antigen‐Specific T Cell Proliferation in MS Patients

Abstract: Current theories of multiple sclerosis (MS) induction and progression place autoreactive T cells in the focus of the pathogenesis. Mesenchymal/stromal stem cells (MSC) have become a promising alternative approach for pathogenic therapy of MS due to their immunomodulatory properties, underlying mechanisms of which are intensive study. The objective of the research was to investigate the contribution of PGE 2 to MSC-mediated suppression in patients with MS using in vitro model of mitogen-and myelin-stimulated T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
3
17
0
1
Order By: Relevance
“…The increased secretion of PGE-2 by all pre-treated hMSC groups therefore indicates that, regardless of the cell culture process steps utilised, all of the cells demonstrated an immunosuppressive response to an inflammatory microenvironment. Previous experiments have reported a similar magnitude of PGE-2 secretion in mice and human MSCs after alternative pretreatment and co-culture [56,57].…”
Section: Pge-2 Quantificationsupporting
confidence: 57%
“…The increased secretion of PGE-2 by all pre-treated hMSC groups therefore indicates that, regardless of the cell culture process steps utilised, all of the cells demonstrated an immunosuppressive response to an inflammatory microenvironment. Previous experiments have reported a similar magnitude of PGE-2 secretion in mice and human MSCs after alternative pretreatment and co-culture [56,57].…”
Section: Pge-2 Quantificationsupporting
confidence: 57%
“…response [34,35,40,41]. However, PGE2 has also been implicated as part of the mechanisms mediating anti-inflammatory effects of MSCs, including their capacity to limit T-cell proliferation [42], suppress Th17 responses through cell-contact-mediated inhibition [43], induce regulatory T-cell responses [16], and inhibit gd T cells and invariant natural killer T-cell expansion [44].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MSCs imposed durable suppression on antigendriven memory T-cell proliferation, which persisted during subsequent cycles of antigen restimulation even though they were no longer present in cocultures [15,36 & ]. Moreover, prostaglandin E 2 (PGE 2 ) concentrations in the supernatants of these cocultures correlated with the index of MSC-mediated suppression of myelin-induced T-cell proliferation [38]. Although MSCmediated immunosuppressive activity is not MHCrestricted, a study using in-vitro cocultures of MSCs and peripheral blood mononuclear cells (PBMCs) of patients with multiple sclerosis revealed that the inhibitory effect of MSCs on myelin-induced memory T-cell proliferation was stronger than that on mitogen-stimulated proliferation [37 & ].…”
Section: Effects Of Mesenchymal Stromal Cells On Memory T Cells In Vitromentioning
confidence: 99%